Identification of Medicinal Plants in UIN Kiai Haji Achmad Siddiq Jember - Hasanah, Susi Faheliyatul; Maftuhah, Laila; Mahfud, Nauval Abdulloh; Dalilah, Na'ilah Abidah (META: Journal of Science and Technological Education, 2023)
Due to Indonesia's high biodiversity, medicinal plants have the potential to become alternative treatments and boost national economic competitiveness. The investigation was conducted during November in 2022. This research was conducted to acquire information about medicinal plants in the research location in order to expand knowledge about medicinal plants and provide the area management with additional data. This research's main objective is to develop the potential of medicinal plants near UIN KHAS Jember in an endeavor to enhance the health of campus residents. Secondary goals of this research include learning how to use medicinal plants, how to obtain medicinal plants, and the varieties of medicinal plants used by the UIN KHAS Jember community. An exploratory survey and interviews with the residents of UIN KHAS Jember are employed. Community participation was obtained using a semi-structured interview technique accompanied by a list of queries such as the local name of the plant, the part used, its benefits, how to use it, etc. Each plant used as a constituent in traditional medicine is identified.